2015
DOI: 10.1016/j.jvs.2015.04.460
|View full text |Cite
|
Sign up to set email alerts
|

Results of the ROADSTER multicenter trial of transcarotid stenting with dynamic flow reversal

Abstract: The results of the ROADSTER trial demonstrate that the use of the ENROUTE Transcarotid NPS is safe and effective at preventing stroke during CAS. The overall stroke rate of 1.4% is the lowest reported to date for any prospective, multicenter clinical trial of CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(228 citation statements)
references
References 27 publications
5
213
1
1
Order By: Relevance
“…2 The patient’s visual symptoms disappeared immediately after this procedure, and she was found to be in good health in clinic 1 month and then 5 months after the procedure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2 The patient’s visual symptoms disappeared immediately after this procedure, and she was found to be in good health in clinic 1 month and then 5 months after the procedure.…”
Section: Discussionmentioning
confidence: 91%
“…The patient’s atorvastatin was increased from 10 mg to 40 mg once daily. The patient was referred to a vascular surgeon, who recommended performing brachiocephalic stenting retrogradely as previously reported 2 (Figure 2). The patient tolerated the procedure well, without procedure or postoperative complications.…”
Section: Managementmentioning
confidence: 99%
“…Not long ago, the Reverse Flow Used During CAS Procedure (ROADSTER) multicenter trial reported its results from the evaluation of the safety and efficacy of the ENROUTE Transcarotid NPS (Silk Road Medical Inc, Sunnyvale, Calif), a novel transcarotid neuroprotection system that provides direct surgical common carotid access and cerebral embolic protection via high-rate flow reversal during CAS[29]. This study reported an overall stroke rate of 1.4%, which is the lowest reported for any prospective multicenter clinical trial of CAS.…”
Section: Transcervical Access With Flow-reversalmentioning
confidence: 99%
“…This study reported an overall stroke rate of 1.4%, which is the lowest reported for any prospective multicenter clinical trial of CAS. The stroke/death rates (2.8%) and the stroke/death/MI rates (3.5%) reported were also similarly low[29]. …”
Section: Transcervical Access With Flow-reversalmentioning
confidence: 99%
“…The symptomatic transformation of atherosclerotic CS, however, is far from being eradicated. Consequently, contemporary carotid revascularization studies [11][12][13] continue to include up to 55% symptomatic subjects in all-comer patient series. 11 A significant proportion of these patients are already on antiplatelet and maximized statin treatment prior to the CS-associated stroke events, 11,14,15 consistent with the fact that medical therapy reduces but does not abolish the CS stroke risk.…”
Section: Pharmacologic Therapymentioning
confidence: 99%